A new genus and new species of Sclerodactylidae (Holothuroidea: Dendrochirotida) from the south-western Atlantic coast - Martins, Luciana; Souto, Camilla; Menegola, Carla (Zootaxa, 2012)
In this paper, we diagnose a new genus of Sclerodactylidae, Coronatum gen. et sp. nov., from shallow waters of the south-western Atlantic Ocean. Coronatum baiensis sp. nov. has a compact calcareous ring with short posterior processes and aunique set of body wall ossicles, composed of two-pillared tables, which do not have any morphological affinities withEuthyonidiella dentata and Pseudothyone belli, the other two known Brazilian sclerodactylid species. Identification keysand photographs of living specimens and ossicles are provided. This paper increases to twelve the number of known Sclerodactylinae genera and to two the number of species of this subfamily in this region.